Analisis Uji Organoleptik Sambal Ebi Mangrove Khas di Ekowisata Mangrove Wonorejo - erlinda shella ramadhanty; Marmi; Sukian Wilujeng; Pramita Laksitarahmi Isrianto; Sunaryo (Universitas Pendidikan Ganesha, 2024)
Wonorejo Mangrove Ecotourism is one of the tourist attractions in the East Surabaya area which is rich in natural resources. The potential of this mangrove resource is not only to support the activities of the surrounding community, but also students and students. Currently, mangroves are not only used as barriers to sea water abrasion, but can also be processed into potential food raw materials. However, not all types of mangroves can be processed into food, only a few types can be processed, one of which is pedada fruit (Sonneratia caseolaris). Pedada fruit is one of the mangrove fruits which is often processed into food ingredients such as syrup, jam, chili sauce, dodol, coffee, chips, flour, and so on. This research was conducted to utilize mangrove fruit to add economic value and improve livelihoods for local communities, as well as to provide information to the general public about the benefits of mangroves as food, drinks, medicines and even cosmetics.